Translations of Foreign Poetry. Translation of Garcilaso de la Vega's Poetry into Ukrainian (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
Kvachuk M. Translation of Garcilaso de la Vega's Poetry into Ukrainian